Asia’s Chemical Distribution Market: The final Frontier for Mergers and Acquisitions! - Bee, Tay Kin (Archives of Business Research, 2021)
The chemical distribution business had undergone huge transformational changes globally, through mergers and acquisitions, by both strategic buyers and private equity firms. The industry consolidation process in Europe and North America which started many years ago is now being shifted to Asia. There is very little research being done on Asia’s chemical distribution market size and the major chemical distributors. Asia’s chemical industry enjoyed tremendously high growth in the past years, and coupled with the highly fragmented chemical marketplace, it offers huge scope for consolidation. The lack of information and clarity in Asia’s chemical distribution sector has somewhat impeded the pace of the consolidation process. A clearer knowledge of the chemical distribution market size, and the key players in the market, itself would help potential investors enormously in their decision making to expedite the mergers and acquisitions process. The research findings can serve as a compass for potential investors to navigate through Asia when searching out for potential targets and would offer investors a much-needed informational tool to know where to look to invest in. Literature review on existing publications, chemical industry trade publications, and chemical distribution associations will provide the background information for this research.